Boosting the thermoelectric performance of p-type polycrystalline SnSe with high doping efficiency via precipitation design. Issue 5 (15th January 2021) - Li, Chengjun; Peng, Kunling; Wu, Hong; Li, Nanhai; Zhang, Bin; Wang, Guiwen; Gong, Xiangnan; Lu, Xu; Wang, Guoyu; Zhou, Xiaoyuan
Abstract : High performance was achieved in polycrystalline SnSe via optimizing electrical transport properties and microstructure design. Abstract : Polycrystalline SnSe has been widely studied in recent years due to its potential in thermoelectric applications. However, the carrier concentration and electrical performance have not been effectively optimized due to the low doping efficiency for most of the reported polycrystalline SnSe systems. Herein, we report a high power factor (PF) of 0.89 mW m −1 K −2 at 790 K in p-type polycrystalline SnSe, which benefits from the significantly optimized carrier concentration by (Na and Ag) co-doping and the enhancement of the Seebeck coefficient due to the increase of band effective mass via Te alloying. Meanwhile, the coexistence of Ag and Te rich precipitates and the increased grain boundaries in the bulk impressively reduce the lattice thermal conductivity to 0.36 W m −1 K −1 at 790 K along the direction perpendicular to the pressure. Consequently, a high thermoelectric figure of merit zT of 1.47 at 790 K and an average zT of 0.67 over the measured temperature range have been achieved in the polycrystalline SnSe sample.